1995
DOI: 10.1002/ajpa.1330960203
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA of the Mauritian macaques (Macaca fascicularis): An example of the founder effect

Abstract: Macaque monkeys (Macaca fascicularis) were introduced to the island of Mauritius approximately 400 years ago. This study compares the mitochondrial DNA of macaques on Mauritius with those from Indonesia and the Philippines. The goal is to measure the amount of evolutionary change that has occurred in this isolated population over 400 years, and to address questions regarding the origin of the Mauritian founders. Amplification of the control region of the mitochondrial genome via the polymerase chain reaction y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 32 publications
8
71
1
Order By: Relevance
“…Anthropological and historical evidence suggests that the macaques were introduced to the island ϳ400 years ago by European seafarers (60). mtDNA analysis of Mauritian origin macaques supports the existence of a population bottleneck at the time of introduction; in fact, the founding population may have included only a single female (61). Although low mtDNA divergence does not necessarily correlate with low nuclear gene variability, other studies have found the genetic diversity of nuclear genes in this population is lower than in Asian origin Cynomolgus macaques (62).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Anthropological and historical evidence suggests that the macaques were introduced to the island ϳ400 years ago by European seafarers (60). mtDNA analysis of Mauritian origin macaques supports the existence of a population bottleneck at the time of introduction; in fact, the founding population may have included only a single female (61). Although low mtDNA divergence does not necessarily correlate with low nuclear gene variability, other studies have found the genetic diversity of nuclear genes in this population is lower than in Asian origin Cynomolgus macaques (62).…”
Section: Discussionmentioning
confidence: 89%
“…Mauritius is Ͻ2000 km (2), with unequal monkey distribution throughout the small island. Previous analysis of mtDNA using monkeys captured from different sites did not observe genetic stratification by habitat, providing anecdotal evidence that subpopulations of macaques on the island are genetically homogenous (61). Do Mauritian origin Cynomolgus macaques represent a reasonable alternative animal model for AIDS research?…”
Section: Discussionmentioning
confidence: 99%
“…The limited MHC repertoire of MCM may reflect selective advantages of these haplotypes for the Mauritian environment. It appears more likely that the limited MHC diversity described here is the result of a classic population bottleneck or founder effect (22,30,36; A. J. Tosi and C. S. Coke, submitted for publication). Consequently, there is little reason to assume that the relative genetic homogeneity of MCM is restricted to the MHC.…”
Section: Vol 81 2007mentioning
confidence: 90%
“…MCMs are a geographically isolated population descended from a small founder population over the last 500 years (19). Consequently, MCMs have extremely simple MHC genetics consisting of seven major haplotypes, termed M1 to M7 (2,29).…”
Section: T Cell Responses In Mhc-i Homozygous Mauritian Cynomolgus Mamentioning
confidence: 99%